Crime-associated inequality in geographical access to education: Insights from the municipality of Rio de Janeiro - Knoblauch, Steffen; Muthusamy, Ram Kumar; Moritz, Maya; Kang, Yuhao; Li, Hao; Lautenbach, Sven; Pereira, Rafael H. M.; Biljecki, Filip; Gonzalez, Marta C.; Barbosa, Rogerio; Hirata, Daniel Veloso; Ludwig, Christina; et al. (Cities, 2025)
Education is a fundamental right, supported by initiatives like Education for All (EFA) and the Millennium Development Goals (MDGs). Despite progress, full educational access remains challenging, particularly in highly criminal areas. This paper examines the impact of crime on school access in the municipality of Rio de Janeiro. Using ancillary data and geospatial artificial intelligence (GeoAI), we downscaled official police crime records to street level. By considering different levels of crime tolerance in school path choices, we simulated how crime can force students to walk longer distances to avoid violence. Our findings indicate a 48.60 % average increase in travel time to the closest school for students whose shortest routes intersect with high-crime areas. This adjustment reduces mean crime exposure by 44.10 % and maximum exposure by 81.94 %. Both individual crime risk aversion and no-go areas of criminal disputes significantly (p ≤ 0.05) impacted educational access. Estimating street-level crime exposure was challenging due to spatial bias in official and crowdsourced crime reporting. These methods and insights are crucial for improving educational access in high-crime areas, providing a better understanding of barriers to equitable education, and being applicable to other cities and accessibility studies for various societal needs.